2017
DOI: 10.1002/aoc.3792
|View full text |Cite
|
Sign up to set email alerts
|

Role of Knoevenagel condensate pyrazolone derivative Schiff base ligated transition metal complexes in biological assay and cytotoxic efficacy

Abstract: A new bioessential Knoevenagel condensate Schiff base ligand (L) was synthesized by the reaction of 3‐(4‐hydroxy‐3‐methoxybenzyl)pentane‐2,4‐dione and 4‐aminoantipyrine. The ligand forms monomeric divalent transition metal complexes (1–4) which were characterized using spectral and analytical data. All these complexes have the general formula [ML]Cl2, where M = Co(II), Ni(II), Cu(II) and Zn(II). They are electrolytic in nature and adopt square planar geometry. The binding propensity of these complexes with cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…These results are consistent with findings reported in previous studies that investigated the cytotoxicity of pyrazolone compounds against cell lines. After treatment of MCF‐7 cells with a Zn II compound containing a tetradentate pyrazolone Schiff base ligand, Paulpandiyan et al found an IC 50 value of 28 µ m , that is higher than our values . Another study by Zong et al revealed a decrease of cell viability ranging from 20 % to 80 % after 24 h of treatment with other Zn II compounds containing pyrazolone‐enamine ligands at concentration of 40 µ m , even if they used different cell lines (human breast cancer MDA‐MB‐231) .…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…These results are consistent with findings reported in previous studies that investigated the cytotoxicity of pyrazolone compounds against cell lines. After treatment of MCF‐7 cells with a Zn II compound containing a tetradentate pyrazolone Schiff base ligand, Paulpandiyan et al found an IC 50 value of 28 µ m , that is higher than our values . Another study by Zong et al revealed a decrease of cell viability ranging from 20 % to 80 % after 24 h of treatment with other Zn II compounds containing pyrazolone‐enamine ligands at concentration of 40 µ m , even if they used different cell lines (human breast cancer MDA‐MB‐231) .…”
Section: Resultscontrasting
confidence: 73%
“…After treatment of MCF-7 cells with a Zn II that is higher than our values. [58] Another study by Zong et al revealed a decrease of cell viability ranging from 20 % to 80 % after 24 h of treatment with other Zn II compounds containing pyrazolone-enamine ligands at concentration of 40 μM, even if they used different cell lines (human breast cancer MDA-MB-231). [59] A strong decline of MCF-7 cell viability (95 %) was found in our study at concentration of 50 μM after treatment with the complex 4.…”
Section: Cytotoxicity Studiesmentioning
confidence: 99%
“…It is also revealed that the enhanced antibacterial activity could be attributed to changes in pharmacological kinetics, conductivity, steric, electronic, solubility, and metal-ligand bond length. The difference in the antimicrobial efficacy of some of the compounds towards various microorganisms influences on the impermeability of the cells of the germs or the diversity of ribosomes of the microbes [ 124 ]. The % of the inhibition of all substances is estimated from ( 45 ) ( Table 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Copper complexes exhibit only one bond in region 19,920–20,243 cm −1 , which is assigned to 2B 1g → 2A 1g (ʋ 1 ) transition, a characteristic bond of square planar geometry around copper centers and the magnetic moment values lie in range 1.47–1.49 BM, tells about presence of one unpaired electron in copper complexes. [ 28,39 ]…”
Section: Resultsmentioning
confidence: 99%